The Effect of Foreign Direct Investment, Inflation, and Labor Force Participation Rate on National Income of Asean Countries In 2010-2020 - Muhammad Iqbal; Dedi Budiman Hakim; Lukytawati Anggraeni (Green Publisher Indonesia, 2025)
Capital availability is necessary to support economic growth in order to reach its potential. Sources of capital supply might come from various sources owned by the state or foreigners. One of the foreign capital supplies comes from foreign direct investment (FDI). Recently, FDI is known to be one of the factors driving the national income of various countries in the world, including ASEAN countries. This study examines the influence of FDI, inflation, and the labor force participation rate (TPAK) on GDP in ASEAN countries. This study used secondary data in the form of panel data from eleven ASEAN countries for the period 2010 to 2020. The analytical method involved using the static panel analysis with the best model in the form of a fixed effect model (FEM) equipped with descriptive statistical analysis for each variable in this study. The results confirmed that FDI has a positive and significant effect on GDP. Meanwhile, inflation and TPAK has a negative and significant impact on nominal GDP in ASEAN countries over the time span of observation. For this reason, the governments of each country need to formulate strategies and policies to encourage investment improvement and economic stability. This is important to support each country's economy to achieve its best potential.